Static Young's Modulus Prediction of Shale Formations Using Well Log Data: A case study from Rumaila oilfield - Mahdi, Doaa Saleh; A.Alrazzaq, Ayad A.Alhaleem (Iraqi Journal of Science, 2025)
Static young modules (Est) can be measured in the lab on real cores. Moreover, open-hole log data can be utilized to obtain the dynamic Young's modulus (Edyn). However, dynamic Young's modulus is affected by different rock properties. Thus, dynamic rock properties must be changed to static moduli using empirical equations. In this study, an experimental dataset from shale formation has been used to produce a reliable and accurate correlation for estimating static Young's modulus from log data alone, without the need for core measurements. We used 144 data points from log data to create the new correlations. We compared the results of the new correlation with earlier correlations in the literature. The findings demonstrated that, in contrast to those in the literature, the proposed empirical correlation is accurate and dependable with a correlation coefficient (RSQ) of 0.97% and an average absolute error (AAER) of 9.69%. Therefore, the new correlation can be used to improve shale formation fracturing operations, resolve issues related to shale instability, and optimize drilling procedures such as bit type and drilling parameters.